Translation and Validation of the Pelvic Floor Distress Inventory Short Form (PFDI-20) to Urdu Language (Journal of Medical & Health Sciences Review, 2025)
Pelvic floor issues are distressing for postmenopausal women. Pelvic floor distress inventory short form (PFDI-20) is translated and validated into many languages to determine pelvic floor disorders in those populations. There was a need to translate and validate this tool to Urdu language.Objective: To translate Pelvic floor distress inventory short form (PFDI-20) into Urdu language and determine validity and reliability of Urdu version of (PFDI-20).Methods: This validation study was conducted at Riphah International University, Islamabad. Pelvic floor distress inventory short form (PFDI-20) Questionnaire was translated into Urdu language by Urdu translators and bilingual medical professional using WHO method. Final approved version was applied to menopausal women with at least one symptom of pelvic floor disorders.Results:Data was obtained from 85 menopausal women. Mean scoring obtained was 41±26.  Data was obtained at time (T1) and then after few weeks at time (T2). For PFDI-20(URDU) and Sub scales (POPDI-6, CRSDI-8 and SUI-6), there was no significant difference between the test and retest scores. Value for Cronbach’s Alpha was 0.966. Pearson’s correlation between PFIQ-7 and PFDI-20 and its subscales was 0.450, showing moderate correlation.Conclusion:The study indicates that, PFDI-20 Scale of Urdu version is a valid and reliable tool. This tool can be used for clinical and research purpose.